Pleomorphic Adenoma of Minor Salivary Gland in Parapharyngeal Space - Jain, Leena; Qureshi, Sadat; Maurya, Ashish; Jadia, Shalini (Journal of Orofacial Research, 2013)
A case of pleomorphic adenoma of minor salivary gland in parapharyngeal space is being reported as the incidence of pleomorphic adenoma of minor salivary gland in parapharyngeal space is of very rare occurrence. Transpalatal complete excision of tumor was done under general anesthesia.